2020
DOI: 10.1038/s12276-020-0464-3
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cells undergoing epigenetic transition show short-term resistance and are transformed into cells with medium-term resistance by drug treatment

Abstract: To elucidate the epigenetic mechanisms of drug resistance, epigenetically reprogrammed H460 cancer cells (R-H460) were established by the transient introduction of reprogramming factors. Then, the R-H460 cells were induced to differentiate by the withdrawal of stem cell media for various durations, which resulted in differentiated R-H460 cells (dR-H460). Notably, dR-H460 cells differentiated for 13 days (13dR-H460 cells) formed a significantly greater number of colonies showing drug resistance to both cisplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Total RNA was extracted with TRIzol (#15596026, Invitrogen) and RNA sequencing was performed by the Macrogen (Seoul, Korea) according to the method described previously [ 23 ]. Briefly, total RNA concentration was calculated by Quant-IT RiboGreen (Invitrogen, #R11490).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted with TRIzol (#15596026, Invitrogen) and RNA sequencing was performed by the Macrogen (Seoul, Korea) according to the method described previously [ 23 ]. Briefly, total RNA concentration was calculated by Quant-IT RiboGreen (Invitrogen, #R11490).…”
Section: Methodsmentioning
confidence: 99%
“…A heatmap of DEGs was created using a MultiExperiment Viewer (The Institute of Genomic Research, Rockville, MD, USA). DEGs were subjected to core analysis using Ingenuity Pathway Analysis (IPA) software (Qiagen, Hilden, Germany), as described previously [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analyses were performed as described previously [ 50 ]. P values were calculated using GraphPad version 7.0d (GraphPad Software Inc., Cary, NC, USA), and those less than 0.05 were considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple omics data are often generated to examine various biological aspects of drug-resistant cancer cells (Figure 1). Target genotypes and phenotypes examined using omics data (Table 1) include: cancer-associated mutations (Niehr et al, 2018;Marczyk et al, 2020;Sinkala et al, 2021); changes in the expression level of specific genes (Niehr et al, 2018;Nava et al, 2019;Kagohara et al, 2020;Marczyk et al, 2020;Poojan et al, 2020;Sinkala et al, 2021); changes in chromosome structure (Kagohara et al, 2020;Marczyk et al, 2020;Aissa et al, 2021); epigenetic alterations (e.g., methylation or acetylation states of histone • Methylome (reduced representation bisulfite sequencing)…”
Section: Multi-omics Analysesmentioning
confidence: 99%
“…• ceRNA network for correlation between lncRNA and mRNA levels using RNA-seq data proteins) (Nava et al, 2019;Kagohara et al, 2020;Marczyk et al, 2020;Poojan et al, 2020;Sinkala et al, 2021); and the presence of heterogeneity of a cell population (Niehr et al, 2018), often increasingly examined at a single-cell resolution (Kagohara et al, 2020;Aissa et al, 2021). In a recent study for cell line heterogeneity, for example, application of single-cell DNA and RNA sequencing (RNA-seq) to 20 triple-negative breast cancer (TNBC) patients revealed that rare pre-existing clones having genotypes associated with chemoresistance were adaptively selected in response to neoadjuvant chemotherapy, which subsequently led to acquired transcriptional reprogramming (Kim et al, 2018).…”
Section: Multi-omics Analysesmentioning
confidence: 99%